Efficient Organic Sensitizers with Pyridine‐N‐oxide as an Anchor Group for Dye‐Sensitized Solar Cells. Issue 9 (25th July 2014) - Wang, Lei; Yang, Xichuan; Zhao, Jianghua; Zhang, Fuguo; Wang, Xiuna; Sun, Licheng
Abstract Five organic dyes with pyridine‐N‐oxide as the anchor group and electron acceptor have been synthesized and applied in dye‐sensitized solar cells (DSSCs). Benzothiadiazole was introduced in the conjugation system to increase the electron withdrawing properties, FTIR spectra showed that the coordination was between the pyridine‐N‐oxide and the Brønsted acid site on the TiO2 surface. The relationship between different dye structures and the performance of the DSSCs was investigated systematically. The location of the thiophene unit was studied, and the direct linkage of benzothiadiazole with pyridine‐N‐oxide was beneficial to broaden the absorption. The donor–acceptor–acceptor‐configured dye WL307, which has 2‐ethylhexyloxy chains in the donor part, showed the best efficiency of 6.08 % under 100 mW cm−2 light illumination. The dye series showed a fairly good stability during the one month test period.